Stain-resistant silicone coating composition

By using a combination of polycondensation effective polymer, surface wetting agent, filler and condensation catalyst in silicone elastomer coatings, the problem of both stain resistance and elongation is solved, and efficient stain resistance and protection are achieved .

CN119220172APending Publication Date: 2024-12-31MOMENTIVE PERFORMANCE MATERIALS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411368340.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2016-01-27
Filing Date
2017-01-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing silicone elastomer coatings have shortcomings in their stain resistance and are difficult to maintain elongation when increasing hardness, especially in architectural coating applications.

Method used

Elastomer coating compositions including polycondensation effective polymers with more than two silicon atoms, surface wetting agents, fillers and condensation catalysts, improve stain resistance by combining polyether silanes with layered structural fillers (such as mica) , while maintaining the elasticity and elongation of the paint.

Benefits of technology

The coating has significantly improved its stain resistance without adversely affecting other properties, providing good UV, weathering and water protection, and avoiding overhardening and peeling of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005066873670000031
    Figure BDA0005066873670000031
  • Figure BDA0005066873670000032
    Figure BDA0005066873670000032
  • Figure BDA0005066873670000041
    Figure BDA0005066873670000041
Patent Text Reader

Abstract

The invention relates to a silicone coating composition, an architectural coating, a once-coated stain-resistant and / or stain-resistant and / or anti-fouling coating, and a method for producing an elastomeric coating composition. The elastomeric coating composition includes (a) at least one polycondensation-effective polymer having two or more silicon atoms; (b) a surface wetting agent; (c) a filler; (d) a condensation catalyst; and (e) optionally, one or more cross-linking agents.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application with application number 201780008473.8, application date January 25, 2017, and invention name “Anti-fouling silicone coating composition”.

[0002] This application claims priority to provisional U.S. patent application No. 62 / 287,647, filed on January 27, 2016, the entire contents of which are incorporated herein by reference. Technical Field

[0003] Provided herein is a silicone coating composition, and more particularly a silicone coating composition that exhibits lower dirt pick up than conventional silicone coatings. Background Art

[0004] Coatings have been widely used in many fields. In the use of silicone elastomeric coatings, properties such as water resistance, durability, flexibility, and resistance to UV and thermal cracking are important in various applications in which the silicone elastomeric coatings are used. Due to the low glass transition temperature (Tg) of silicone, elastomeric coatings containing silicone have a softer outer surface, which leads to stickiness and increased staining.

[0005] The traditional approach for improving stain resistance is to increase the Tg of the coating, essentially creating a harder outer surface at the expense of elongation. Therefore, one of the challenges has always been to achieve an optimal hardness level without compromising elongation values, both of which are important in architectural coating applications.

[0006] Other approaches to improving stain resistance have included the use of highly cross-linked polymers, which result in a low-tack surface that hinders stain penetration. While this approach is commonly used in automotive coating applications and architectural organic coatings, silicone elastomeric coatings offer unique challenges, including the need to retain a minimum level of elongation.

[0007] Therefore, there still exists a need for a silicone-based elastomeric coating composition that not only improves stain resistance but also simultaneously overcomes other problems that conventional silicone-based elastomeric coating compositions have not yet satisfactorily addressed. Summary of the invention

[0008] According to the present invention, one aspect provides an elastomeric coating composition comprising:

[0009] a) at least one condensation-polymerizable polymer having (carrying) two or more silicon atoms;

[0010] b) a surface wetting agent selected from the group consisting of polyoxyalkylene-containing silanes, heteroatom-containing silanes, functionalized organosiloxanes, and combinations thereof, wherein the polyoxyalkylene-containing silanes comprise an aliphatic hydrocarbon moiety between the silicon atom and the polyoxyalkylene moiety in the polyoxyalkylene-containing silanes;

[0011] c) at least one filler;

[0012] d) a condensation catalyst; and,

[0013] e) optionally one or more cross-linking agents.

[0014] Additionally provided herein is a method of making an elastomeric coating composition comprising combining components (a)-(d) and optionally (e).

[0015] The present invention includes the following embodiments:

[0016] 1. An elastomeric coating composition comprising:

[0017] a) at least one condensation-polymerizable polymer of formula (I) having two or more silicon atoms;

[0018] M 1 a M 2 b M 3 c M 4 d D 1 e D 2 f D 3 g D 4 h (I)

[0019] in:

[0020] M 1 =R 1 R 2 R 3 SiO 1 / 2

[0021] M 2 =R 4 R 5 R 6 SiO 1 / 2

[0022] M 3 =R 7 R 8 R 9 SiO 1 / 2

[0023] M 4 =R 10 R 11 R 12 SiO 1 / 2

[0024] D 1 =R 13 R 14 SiO 2 / 2

[0025] D 2 =R 15 R 16 SiO 2 / 2

[0026] D 3 =R 17 R 18 SiO 2 / 2

[0027] D 4 =R 19 R 20 SiO 2 / 2

[0028] Among them, R 1 and R 13 Each is independently an aliphatic group or an aromatic group having 1 to 60 carbon atoms, OH or -H or OR 25 , where R 25 is an aliphatic or aromatic group having 1 to 60 carbon atoms;

[0029] R 2 , R 3 , R 5 , R 6 , R 8 , R 9 , R 10 R 11 , R 12 , R 14 , R 16 , R 18 , R 19 and R 20 Each independently is an aliphatic or aromatic group having 1 to 60 carbon atoms;

[0030] R 4 and R 15 Each independently is as follows:

[0031] -(C n H 2n )-O-(C2H4O) o -(C3H6O)p -(C4H8O) q -R 26 , where R 26 is hydrogen or an aliphatic or aromatic group having 1 to 60 carbon atoms, n is 0 to 6, o is 0 to 100, p is 0 to 100, and

[0032] q is 0-50, provided that o+p+q≥0;

[0033] R 7 and R 17 are each independently a branched, linear or cyclic saturated or unsaturated alkyl group having 4 to 36 carbon atoms, and

[0034] The subscripts a, b, c, d, e, f, g, h are each independently zero or a positive integer, and the prerequisite is that a+b+c+d+e+f+g+h≥2, and a+b+c+d=2, and a+e≥2, and

[0035] Provided that the polymer of formula (I) comprises a group consisting of -OH, -OR 25 and combinations thereof of at least two groups;

[0036] b) a surface wetting agent selected from the group consisting of polyoxyalkylene-containing silanes, heteroatom-containing silanes, functionalized organosiloxanes, and combinations thereof, wherein the polyoxyalkylene-containing silanes comprise an aliphatic hydrocarbon moiety between the silicon atom and the polyoxyalkylene moiety of the polyoxyalkylene-containing silane;

[0037] c) at least one filler; and,

[0038] d) Condensation catalyst.

[0039] 2. The elastomeric coating composition of item 1, wherein the at least one condensation-polymerizable polymer having two or more silicon atoms (a) is selected from the group consisting of hydroxyl-terminated polydimethylsiloxane, alkoxy-terminated polydimethylsiloxane, and combinations thereof.

[0040] 3. The elastomeric coating composition of item 1, wherein the at least one condensation-polymerizable polymer having two or more silicon atoms (a) is a silanol-terminated polydiorganosiloxane wherein each organic moiety is independently an alkyl group having 1 to about 6 carbon atoms.

[0041] 4. The elastomeric coating composition of item 1, wherein the surface wetting agent (b) is a polyoxyalkylene-containing silane selected from the group consisting of general formula (II) and / or (III), wherein formula (II) is:

[0042]

[0043] Where R27 independently selected from alkyl groups having 1 to about 12 carbon atoms;

[0044] R 28 A portion selected from the following:

[0045]

[0046]

[0047] in represents the bonds connecting the silicon atoms of the structure of formula (II);

[0048] R 29 independently selected from hydrogen or an alkyl radical having 1 to about 4 carbon atoms, or -COR 33 ;

[0049] R 33 independently selected from hydrogen or an alkyl group having 1 to about 16 carbon atoms;

[0050] R 30 independently selected from hydrogen or an alkyl group having 1 to about 4 carbon atoms;

[0051] R 31 independently selected from divalent alkylene groups having 1 to about 4 carbon atoms;

[0052] R 32 independently selected from divalent carbamate, acrylamide, amide or urea groups; and,

[0053] r is 1 to about 100 and x is zero or 1;

[0054] Wherein formula (III):

[0055]

[0056] Where R 27 For previously defined;

[0057] Z is independently selected from divalent carbamate, acrylamide, amide or urea groups;

[0058] s and t are independently integers from 0 to 2;

[0059] L is independently selected from divalent aliphatic linear hydrocarbon groups having 2 to about 15 carbon atoms and can optionally have oxygen or nitrogen atoms at one or both valence bonds;

[0060] R 34 Defined by general formula (IV):

[0061]

[0062] Where R 35 independently selected from hydrogen or an alkyl group having 1 to 4 carbon atoms; x is as previously defined; and u is an integer from 1 to about 100.

[0063] 5. The elastomeric coating composition of item 1, wherein the surface wetting agent (b) is selected from:

[0064] Functionalized organosiloxane of general formula (V):

[0065]

[0066] Where R 39 , R 42 , R 43 , R 44 , R 45 , R 46 , R 47 , R 49 and R 50 independently selected from hydrogen, an alkyl group containing 1 to about 10 carbon atoms, or an alkoxy group containing 1 to about 10 carbon atoms;

[0067] R 40 is selected from hydrogen, an alkyl group containing 1 to about 10 carbon atoms, an alkoxy group containing 1 to about 10 carbon atoms, and a heteroatom-containing compound containing 1 to about 10 carbon atoms, wherein m, n and o are each independently an integer from 0 to about 1000; and

[0068] Compounds of formula (VII)

[0069] R j 41 -ZR k 41 -Z-R1 41 (VII)

[0070] Where R 41 independently selected from hydrogen or an alkyl group having 1 to about 10 carbon atoms or a heteroatom-containing compound having 1 to about 10 carbon atoms;

[0071] Z is a heteroatom, and j, k and l are each independently an integer from 0 to about 10, and

[0072] R 48 and R 51 Independently selected from hydrogen, or hydroxy, or alkyl or alkoxy having 1 to about 10 carbon atoms, or substituted or unsubstituted aromatic compounds containing 6 to about 20 carbon atoms.

[0073] 6. The elastomeric coating composition of item 1, wherein the surface wetting agent (b) is one or more selected from the following: silanes containing ethylene oxide and / or propylene oxide; functional siloxanes selected from polyether functionalized polydimethylsiloxanes, polyether functionalized trisiloxanes, low molecular weight end-capped polydimethylsiloxanes having a viscosity of 2,000-10,000 cps, high molecular weight end-capped polydimethylsiloxanes having a viscosity of 30,000-40,000 cps, eugenol end-capped polydimethylsiloxanes, dimethoxy-methyl end-capped polydimethylsiloxanes, methyl end-capped polydimethylsiloxanes, and combinations thereof.

[0074] 7. The elastomeric coating composition of item 1, wherein the filler (c) is a layered structural filler selected from clay, nanoclay, organoclay, ground calcium carbonate, precipitated calcium carbonate, colloidal calcium carbonate, calcium carbonate treated with a compound containing a stearate moiety or stearic acid, fumed silica, precipitated silica, crushed quartz, quartz powder, alumina, aluminum hydroxide, titanium hydroxide, kaolin, bentonite, montmorillonite, diatomaceous earth, iron oxide, carbon black and graphite, talc, mica, pumice, wollastonite, ceramics, glass beads, PTFE, and combinations thereof.

[0075] 8. The elastomeric coating composition according to item 1, wherein the filler (c) is a wet filler.

[0076] 9. The elastomeric coating composition according to item 1, wherein the filler (c) is mica.

[0077] 10. The elastomeric coating composition of item 1, wherein the surface wetting agent (b) is an oxyethylene and / or oxypropylene-containing silane and the filler (c) is mica.

[0078] 11. The elastomeric coating composition of item 1, wherein the condensation catalyst (d) is a titanium catalyst.

[0079] 12. The elastomeric coating composition of item 1, wherein the condensation catalyst (d) is diisopropyl diacetylacetonato titanium.

[0080] 13. The elastomeric coating composition according to item 1, further comprising a crosslinking agent (e).

[0081] 14. The elastomeric coating composition of item 15, wherein the crosslinking agent (e) is selected from the group consisting of alkoxysilanes, epoxysilanes, mercaptosilanes, acrylate silanes, methacryloxysilanes, vinyl silanes, isocyanatosilanes, and combinations thereof.

[0082] 15. The elastomeric coating composition of item 15, wherein the crosslinking agent (e) is methyltrimethoxysilane.

[0083] 16. The elastomeric coating composition of item 1, further comprising an adhesion promoter selected from the group consisting of tris[3-(trimethoxysilyl)propyl]isocyanurate, 3-isocyanatopropyltrimethoxysilane, α-isocyanatomethyltrimethoxysilane, β-isocyanatoethyltrimethoxysilane, -isocyanatopropyltrimethoxysilane, α-isocyanatomethyltriethoxysilane, β-isocyanatoethyltriethoxysilane, and μ-isocyanatopropyltriethoxysilane isocyanatosilane, 1,3,5-tris(trimethoxysilylpropyl)isocyanurate, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-ethyl-γaminoisobutyltrimethoxysilane, bis-[γ-(trimethoxysilyl)propyl]amine, bis-[γ-(triethoxysilyl)propyl]amine, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, aminopropyltrimethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, trisamino-functional trimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldiethoxy trimethoxysilane, γ-acryloxypropyl trimethoxysilane, γ-methacryloxypropyl methyl dimethoxysilane, γ-glycidyloxypropyl trimethoxysilane, γ-glycidyloxyethyl trimethoxysilane, β-(3,4-epoxycyclohexyl)propyl trimethoxysilane, β-(3,4-epoxycyclohexyl)ethyl methyl dimethoxysilane, isocyanatopropyl triethoxysilane, isocyanatopropyl methyl dimethoxysilane, β-cyanoethyl trimethoxysilane, γ-acryloxypropyl trimethoxysilane, γ-methacryloxypropyl methyl dimethoxysilane, 4-amino-3,3-dimethylbutyl trimethoxysilane, n-ethyl-3-trimethoxysilyl-2-methylpropylamine, or a combination thereof.

[0084] 17. The elastomeric coating composition of item 1, wherein the adhesion promoter is a heteroatom-containing silane having the general formula (VI):

[0085]

[0086] Where R 37 is a divalent alkylene group having 1 to 10 carbon atoms, R 38 is a monovalent hydrocarbon residue having 1 to about 10 carbon atoms, each Y is independently selected from a halogen atom, an alkoxy group having 1 to about 10 carbon atoms, and an acryloxy group having 1 to about 10 carbon atoms, and v is 1-3.

[0087] 18. A building coating comprising the elastomeric coating composition according to item 1.

[0088] 19. A one-time anti-stain and / or anti-fouling and / or anti-fouling coating comprising the elastomeric coating composition according to item 1.

[0089] 20. A method for preparing an elastomeric coating composition, comprising combining:

[0090] a) at least one condensation-polymerizable polymer having two or more silicon atoms;

[0091] b) a surface wetting agent selected from the group consisting of polyoxyalkylene-containing silanes, heteroatom-containing silanes, functionalized organosiloxanes, and combinations thereof, wherein the polyoxyalkylene-containing silanes comprise an aliphatic hydrocarbon moiety between the silicon atom and the polyoxyalkylene moiety in the polyoxyalkylene-containing silanes;

[0092] c) at least one filler; and,

[0093] d) Condensation catalyst. DETAILED DESCRIPTION

[0094] In one embodiment of the present invention, the elastomeric coating composition includes a polyether silane in combination with a filler, such as a lamellar structural filler (e.g., mica). The presence of both the polyether silane and the filler in the coating composition provides improved stain resistance compared to either the polyether silane alone or the filler alone.

[0095] In one embodiment, the coating composition of the present invention can be formulated as an elastomeric coating composition. The term elastomeric according to the present invention means that the composition can provide effective UV, weathering and water protection when applied to a substrate without causing the coating to over-harden over time, which can lead to visible pitting, cracking and peeling of the coating from the substrate. Such elasticity (elastomeric properties) of the coating can be recognized by those skilled in the art through visual inspection of the coating. In one embodiment, the elastomeric advantages of the coating composition can be provided when the coating provides the necessary modulus and elongation levels and the necessary stability and UV resistance levels, as described herein.

[0096] Except in the examples, or where otherwise indicated, all numbers expressing amounts of material, reaction conditions, durations, quantitative properties of materials, and so forth, mentioned in the specification and claims are to be understood as being modified in all instances by the term "about", whether or not the term "about" is used in the phrase.

[0097] It will be understood that any numerical range recited herein, if recited in the examples or anywhere else in the specification, includes all sub-ranges within that range and any combination of endpoints of such ranges or sub-ranges.

[0098] It will also be understood herein that any of the components of the present invention, when they are described by any specific generic concept or a specific generic concept described in the Examples section of the specification, can be used in one embodiment to define an alternative corresponding definition of any endpoint of the range described for that component elsewhere in the specification, and can therefore be used in a non-limiting embodiment to replace the endpoint of the range described elsewhere.

[0099] It will also be understood that any compound, material or substance explicitly or implicitly disclosed in the specification and / or recited in the claims as belonging to a group of structurally, compositionally and / or functionally related compounds, materials or substances includes individual representatives of the group and all combinations thereof.

[0100] According to the present disclosure, reference is made to a substance, component or ingredient that is present just prior to first contact, in-situ formation, blending or mixing with one or more other substances, components or ingredients. A substance, component or ingredient identified as a reaction product, resulting mixture, etc., can acquire an identity, property or characteristic by chemical reaction or transformation during the process of contact, in-situ formation, blending or mixing operations if performed in accordance with the present disclosure using common sense and the ordinary skills of personnel (e.g., chemists) in the relevant field. The conversion of chemical reactants or starting materials to chemical products or final materials is a continuously evolving process, which is independent of the speed at which it occurs. Therefore, when such a conversion process is in progress, there may be a mixture of starting and final materials and intermediate species, which may be easy or difficult to detect by existing analytical techniques known to those skilled in the art depending on their kinetic lifetimes.

[0101] Reactants and components represented by chemical names or formulas in the specification or its claims, whether represented in singular or plural form, can be identified when they exist before contacting other substances represented by chemical names or chemical types (e.g., other reactants or solvents). Preliminary and / or transitional chemical changes, conversions or reactions carried out in the resulting mixture, solution, or reaction medium, if present, can be identified as intermediate species, masterbatches, etc., and can have a utility different from that of the reaction product or final material. Other successive changes, conversions or reactions can be caused by bringing together specified reactants and / or components under conditions required by the present disclosure. In these other successive changes, conversions or reactions, the reactants, ingredients or components brought together can identify or indicate the reaction product or final material.

[0102] In describing the product of the invention as a reaction product of initial materials, the initial species mentioned are mentioned and it should be noted that additional materials may be added to the initial mixture of synthetic precursors. These additional materials may be reactive or non-reactive. A defining feature of the invention is that the reaction product is obtained by the reaction of at least the components listed as disclosed. Non-reactive components are added to the reaction mixture to act as a diluent or to impart additional properties that are unrelated to the properties of the composition prepared as the reaction product. Thus, for example, a particulate solid such as a pigment may be dispersed into the reaction mixture before, during or after the reaction to produce a reaction product composition that additionally includes a non-reactive component such as a pigment. Additional reactive components may also be added; such components may react with the initial reactants or they may react with the reaction product; the term "reaction product" is intended to include the above-mentioned possible substances as well as the addition of non-reactive components.

[0103] As used herein, the phrase "comprising" or "comprises" should also be understood to include the more restrictive transition phrases "essentially consisting of" and "consisting of," which should include components (a)-(d) and optionally (e) described herein, as well as any optional additives described herein, or in more specific embodiments, only components (a)-(d) and optionally (e).

[0104] As used herein with respect to hydrocarbon radicals, the term "monovalent" means that the radical is capable of forming one covalent bond per radical, the term "divalent" means that the radical is capable of forming two covalent bonds per radical, and the term "trivalent" means that the radical is capable of forming three covalent bonds per radical. In general, a monovalent radical may be represented as having been obtained from a saturated hydrocarbon compound by conceptually removing one hydrogen atom from the compound, a divalent radical may be represented as having been obtained from a saturated hydrocarbon compound by conceptually removing two hydrogen atoms from the compound, and a trivalent radical may be represented as having been obtained from a saturated hydrocarbon compound by conceptually removing three hydrogen atoms from the compound. For example, the ethyl radical, i.e., the -CH2CH3 radical, is a monovalent radical; the dimethyl radical, i.e., the -(CH2)2- radical, is a divalent radical and the ethanetriyl radical, i.e.,

[0105]

[0106] The free radicals are trivalent free radicals, each of which can be represented as having been obtained by conceptually removing one or more hydrogen atoms from the saturated hydrocarbon ethane.

[0107] As used herein, the term "hydrocarbon radical", "hydrocarbon group" or "hydrocarbon moiety" all equally refer to a straight chain or branched hydrocarbon radical, preferably containing 1-6 carbon atoms per radical, which may be saturated or unsaturated and may be optionally substituted or interrupted by one or more atoms or functional groups such as carboxyl, cyano, hydroxyl, halogen and oxy. Suitable monovalent hydrocarbon radicals may include, for example, alkyl, alkenyl, alkynyl, hydroxyalkyl, cyanoalkyl, carboxyalkyl, alkoxy, oxaalkyl, alkylcarbonyloxaalkylene, carboxamide and haloalkyl, such as methyl, ethyl, sec-butyl, tert-butyl, vinyl, propenyl, butynyl, hydroxypropyl, cyanoethyl, butoxy, carboxymethyl, chloromethyl and 3,3,3-fluoropropyl.

[0108] Suitable divalent hydrocarbon radicals include, for example, linear or branched alkylene radicals (eg, methylene, dimethylene, trimethylene, ethylethylene, 2-methyltrimethylene, 2,2-dimethyltrimethylene) and linear or branched oxyalkylene radicals (eg, methyleneoxypropylene).

[0109] Suitable trivalent acyclic hydrocarbon radicals include, for example, alkanetriyl radicals (eg, 1,1,2-ethanetriyl, 1,2,4-butanetriyl, 1,2,8-octanetriyl, 1,2,4-cyclohexanetriyl) and oxaalkanetriyl radicals (eg, 1,2,6-triyl-4-oxahexane).

[0110] As used herein, the term "alkyl" means a linear or branched monovalent hydrocarbon radical. In a preferred embodiment, the monovalent alkyl is selected from a linear or branched alkyl containing 1 to 6 carbons per group, such as methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, pentyl and hexyl.

[0111] As used herein, the term "alkenyl" means a straight-chain or branched monovalent terminally unsaturated hydrocarbon radical preferably containing 2-6 carbon atoms per radical, for example, ethenyl, vinyl, allyl, 2-propenyl, 3-butenyl and 5-hexenyl.

[0112] In one non-limiting embodiment herein, some specific non-limiting examples of hydrocarbon radicals that can be used herein are methyl, ethyl, vinyl, allyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl and tert-pentyl; hexyl, such as n-hexyl; and 2,2,4-trimethylpentyl.

[0113] In one embodiment of the present invention, component (a) is a condensation-effective polymer having two or more silicon atoms. As used herein, the term "condensation-effective" is understood to mean that the polymer is capable of condensation by a condensation reaction. Condensation reactions and reaction conditions such as reaction time, temperature and pressure are well known to those skilled in the art.

[0114] In one embodiment, the polycondensation-effective polymer (a) having two or more silicon atoms is preferably a silane and / or an organosilicon compound, more preferably an organosilicon compound in another embodiment, even more preferably a linear organosilicon compound in another embodiment, and most preferably a fully hydroxyl-terminated and / or alkoxy-terminated organosilicon compound in another embodiment. The polycondensation-effective polymer (a) having two or more silicon atoms may more preferably contain at least three silicon atoms, and more preferably about 2 to about 30,000 silicon atoms, even more preferably about 2 to about 20,000 silicon atoms, and even more preferably about 2 to about 10,000 silicon atoms, or any of the ranges has an upper endpoint of any one of 5,000, 3,000, 1,000, 500, 100 or 50 silicon atoms. In one embodiment, any of the silicon atom ranges may include a range of organosilicon units.

[0115] In one embodiment, at least one condensation-polymerizable polymer (a) having two or more silicon atoms is of the general formula (I):

[0116] M 1 a M 2 b M 3 c M 4 d D 1 e D 2 f D 3 g D 4 h (I)

[0117] in:

[0118] M 1 =R 1 R 2 R 3 SiO 1 / 2

[0119] M 2 =R 4 R 5 R 6 SiO 1 / 2

[0120] M 3 =R 7 R 8 R 9 SiO 1 / 2

[0121] M 4 =R 10 R 11 R 12 SiO 1 / 2

[0122] D 1 =R 13 R 14 SiO 2 / 2

[0123] D 2 =R 15 R 16 SiO 2 / 2

[0124] D 3 =R 17 R 18 SiO 2 / 2

[0125] D 4 =R 19 R 20 SiO 2 / 2

[0126] and,

[0127] R 1 and R 13 each independently is an aliphatic or aromatic group having 1 to 60 carbon atoms, more preferably 1 to 20 carbon atoms, even more preferably 1 to about 8 carbon atoms, and most preferably 1 to about 4 carbon atoms, OH, or -H, or OR 25 , where R 25 is an aliphatic or aromatic group having 1 to 60 carbon atoms, more preferably 1 to 20 carbon atoms, even more preferably 1 to about 8 carbon atoms, and most preferably 1 to about 4 carbon atoms;

[0128] R 2 , R 3 , R 5 , R 6 , R 8 , R 9 , R 10 R 11 , R 12 , R 14 , R 16 , R 18 , R19 and R 20 each independently is an aliphatic or aromatic group having 1 to 60 carbon atoms, more preferably 1 to 20 carbon atoms, even more preferably 1 to about 8 carbon atoms, and most preferably 1 to about 4 carbon atoms;

[0129] R 4 and R 15 Each independently is as follows:

[0130] -(C n H 2n )-O-(C2H4O) o -(C3H6O) p -(C4H8O) q -R 26 ,

[0131] Where R 26 is hydrogen, or an aliphatic or aromatic group having 1 to 60 carbon atoms, more preferably 1 to 20 carbon atoms, even more preferably 1 to about 8 carbon atoms, and most preferably 1 to about 4 carbon atoms,

[0132] n is equal to any one of 0-6, preferably 2, 3 or 4, o is 0-100, preferably 1 to about 50, more preferably about 1 to about 30, and most preferably about 1 to about 18, p is 0-100, preferably 0 to about 50, more preferably about 0 to about 30, and most preferably about 0 to about 18, and q is 0-50, preferably 0 to about 18, more preferably about 0 to about 8, and most preferably about 0 to about 1, with the proviso that o+p+q≥0, more particularly with the proviso that o+p+q≥40, even more preferably o+p+q≥18, and most preferably o+p+q≥8;

[0133] R 7 and R 17 each independently is a branched, linear or cyclic saturated or unsaturated alkyl group having 4 to 36, more preferably 1 to 16 and most preferably 1 carbon atom, and

[0134] The subscripts a, b, c, d, e, f, g, h are each independently zero or a positive integer, with the proviso that a+b+c+d+e+f+g+h≥2, more preferably 2-30,000, even more preferably 2-10,000, and most preferably wherein a+b+c+d+e+f+g+h=2 to any endpoint of 5,000, 3,000, 1,000, 500, 100 or 50, and

[0135] a+b+c+d=2,

[0136] And a+e≥2,

[0137] The polymer of formula (I) comprises a group consisting of -OH, -OR 25 and combinations thereof of at least two groups,

[0138] In one embodiment, the at least one condensation-polymerizing effective polymer (a) having more than two silicon atoms is a silanol-terminated polydiorganosiloxane, wherein each organic moiety is independently an alkyl group having 1 to about 6 carbon atoms.

[0139] In another embodiment, the at least one condensation-polymerizing effective polymer (a) having two or more silicon atoms is a mixture of two or more silanol-terminated polydiorganosiloxanes, wherein at least one polydiorganosiloxane has a viscosity of from about 100 cps to about 150,000 cps, preferably from about 1,000 to about 5,000 cps, and even more preferably from about 1,500 to about 4,000, and at least one additional polydiorganosiloxane has a viscosity of from about 10,000 cps to about 80,000 cps, preferably from about 15,000 to about 50,000, and more preferably from about 15,000 to about 40,000. Each reference to viscosity herein is understood to be measured at 25 degrees Celsius unless otherwise stated.

[0140] In another embodiment, the at least one condensation-polymerizable polymer (a) having two or more silicon atoms is a hydroxyl-terminated polydimethylsiloxane, an alkoxy-terminated polydimethylsiloxane, or a polydimethylsiloxane having a combination of hydroxyl and alkoxy termini.

[0141] In one embodiment, the surface wetting agent (b) of the present invention can be selected from polyoxyalkylene-containing silanes, heteroatom-containing silanes, and combinations thereof, wherein the polyoxyalkylene-containing silanes contain an aliphatic hydrocarbon portion between the silicon atom and the polyoxyalkylene portion in the polyoxyalkylene-containing silanes. The polyoxyalkylene portion in the oxyalkylene-containing silanes is a polyoxyethylene- and / or polyoxypropylene-containing silane, preferably a polyoxyethylene-containing silane.

[0142] In one embodiment, the surface wetting agent (b) is a polyoxyalkylene-containing silane selected from the general formula (II) and / or (III):

[0143] Wherein formula (II) is:

[0144]

[0145] Where R 27 independently selected from alkyl groups having 1 to about 12 carbon atoms, preferably 1 to about 8 carbon atoms, and most preferably 1 to about 6 carbon atoms;

[0146] R 28A portion selected from the following:

[0147]

[0148] in:

[0149] represents the bonds connecting the silicon atoms of the structure of formula (II);

[0150] R 29 independently selected from hydrogen or an alkyl group having 1 to 4 carbon atoms (preferably methyl) or -COR 33 ; where R 33 independently selected from hydrogen, or an alkyl group having 1 to about 16 carbon atoms, preferably 1 to about 12 carbon atoms, more preferably 1 to about 8 carbon atoms, and most preferably 1 to about 6 carbon atoms;

[0151] R 30 independently selected from hydrogen or an alkyl group having 1 to 4 carbon atoms, more preferably hydrogen or methyl, and even more preferably hydrogen;

[0152] R 31 Independently selected from divalent alkylene groups having 1 to 4 carbon atoms, more preferably methylene or ethylene;

[0153] R 32 independently selected from divalent carbamate, acrylamide, amide, or urea groups; and,

[0154] r is 1 to about 100, preferably 1 to about 50, and even more preferably 1 to about 25, and x is zero or 1, preferably zero;

[0155] Formula (III):

[0156]

[0157] Where R 27 For previously defined;

[0158] Z is independently selected from divalent carbamate, acrylamide, amide, or urea groups;

[0159] s and t are independently an integer of 0-2, preferably 1;

[0160] L is independently selected from divalent aliphatic linear hydrocarbon groups having 2 to about 15, preferably 3 to 4 carbon atoms and optionally having oxygen or nitrogen atoms at one or both valence bonds;

[0161] R 34 Defined by general formula (IV):

[0162]

[0163] Where R 35 independently selected from hydrogen or an alkyl group having 1 to 4 carbon atoms, preferably hydrogen or methyl, even more preferably hydrogen;

[0164] x is defined previously; and,

[0165] u is an integer from 1 to about 100, more preferably from 1 to about 50, and even more preferably from 1 to about 25. In one embodiment, the surface wetting agent (b) is SILQUEST A-1230 silane, which is available from Momentive Performance Materials Inc.

[0166] In one embodiment, the wetting agent (b) may be a polyether silane, wherein the polyether silane does not have a polyurethane moiety. In another embodiment, the wetting agent (b) is a polyether silane that does not have a halogen moiety and / or a heteroatom (such as O, N and S) and / or an epoxy group.

[0167] In one embodiment, the surface wetting agent (b) is selected from functionalized organosiloxanes of formula (V):

[0168]

[0169] Where R 39 , R 42 , R 43 , R 44 , R 45 , R 46 , R 47 , R 49 and R 50 independently selected from hydrogen, an alkyl group containing 1 to 10 carbon atoms, or an alkoxy group containing 1 to 10 carbon atoms;

[0170] R 40 is selected from hydrogen, an alkyl group containing 1 to 10 carbon atoms or an alkoxy group containing 1 to 10 carbon atoms, a heteroatom-containing compound containing 1 to 10 carbon atoms, or a compound of the general formula (VII), wherein m, n and o are each independently an integer from 0 to about 1000:

[0171] R j 41 -ZR k 41 -Z-R1 41 (VII)

[0172] Where R 41 independently selected from hydrogen, or an alkyl group containing 1 to 10 carbon atoms, or a heteroatom-containing compound having 1 to 10 carbon atoms;

[0173] Z is a heteroatom, and

[0174] R 48 and R 51 is independently hydrogen, or an alkyl or alkoxy group having 1 to 10 carbon atoms, or a substituted or unsubstituted aromatic compound containing 6 to 20 carbon atoms; wherein

[0175] j, k and 1 are each independently an integer from 1 to 10;

[0176] Some non-limiting examples of functionalized siloxanes suitable for use in the present invention include the following structures:

[0177]

[0178] wherein Me means methyl; Z is an alkyl group containing 1 to 4 carbon atoms and m* and n* are each 0 to 10;

[0179]

[0180] wherein Z is an alkyl group having 1 to 4 carbon atoms, m* and n* are each 0 to 10, and x'+y' is 1 to 20;

[0181]

[0182] Where y* is 1-60;

[0183]

[0184] Where y# is 10-1,000;

[0185]

[0186] Where n# is 1-20;

[0187]

[0188] Methyl terminated PDMS, wherein n" is 10-300.

[0189] In one embodiment, the surface wetting agent (b) is one or more selected from the following:

[0190] Silanes containing ethylene oxide and / or propylene oxide;

[0191] an isocyanatosilane selected from tris[3-(trimethoxysilyl)propyl]isocyanurate or 3-isocyanatopropyltrimethoxysilane; and,

[0192] Functional siloxanes selected from the group consisting of polyether functionalized polydimethylsiloxanes, polyether functionalized trisiloxanes, low molecular weight end-blocked polydimethylsiloxanes having a viscosity of 20,00-10,000 cps, high molecular weight end-blocked polydimethylsiloxanes having a viscosity of 30,000-40,000 cps, eugenol end-blocked polydimethylsiloxanes, dimethoxy-methyl end-blocked polydimethylsiloxanes, methyl end-blocked polydimethylsiloxanes, and combinations thereof.

[0193] The at least one filler (c) of the present invention may be any filler that increases the hardness of the composition, but it is more preferably a lamellar structural filler, even more preferably a wet structural filler, although dry structural fillers are also contemplated. Suitable examples of such fillers may be wet fillers (which are made, for example, by the process described in U.S. Pat. No. 3,327,951), and / or dry or wet fillers (which are made by the process described in Industrial Minerals and Rocks, 7th edition, edited by Kozel et al., Society for Mining, Metallurgy, and Exploration Inc., 2006, pp. 647-650), each of which is incorporated herein by reference in its entirety.

[0194] In another non-limiting embodiment, the filler (c) may be selected from clay, nanoclay, organoclay, ground calcium carbonate, precipitated calcium carbonate, colloidal calcium carbonate, calcium carbonate treated with a compound containing a stearate moiety or stearic acid, pyrogenic silica, precipitated silica, crushed quartz, quartz powder, alumina, aluminum hydroxide, ceramic and glass spheres, titanium hydroxide, kaolin, bentonite montmorillonite, diatomaceous earth, iron oxide, PTFE powder, carbon black and graphite, talc, mica, pumice, wollastonite, dolomite, feldspar, and combinations thereof. In one embodiment, the filler (c) may be mica.

[0195] In a further embodiment, the surface wetting agent (b) is a silane containing (poly)ethylene oxide or (poly)propylene oxide, or a combination of the two, and the filler is mica.

[0196] The condensation catalyst (d) that can be used in the present invention may include a metal condensation catalyst, wherein the metal is selected from compounds of tin, titanium, zirconium, lead, iron cobalt, antimony, manganese, bismuth and zinc.

[0197] In one embodiment of the invention, tin compounds can be used as condensation catalysts. Suitable tin compounds may include, but are not limited to, dibutyltin dilaurate, dibutyltin diacetate, dibutyltin dimethanol, tin octoate, isobutyltin triceroate, dibutyltin oxide, dissolved dibutyltin oxide, bis-diisooctylphthalate dibutyltin, bis-tripropoxysilyl dioctyltin, bis-acetylacetonate dibutyltin, silylated dibutyltin dioxide (silylated dibutyltin dioxide), carbomethoxyphenyl tin trisuberate, isobutyltin triceroate, dimethyltin dibutyrate, dimethyltin di-neodecanoate, triethyltin tartrate, dibutyltin dibenzoate, tin oleate, tin naphthenate, tri-2-ethylhexyl hexanoate butyltin, and tin butyrate, combinations thereof, and the like.

[0198] In another embodiment, suitable titanium compounds may also include chelated titanium compounds, such as 1,3-propanedioxytitanium bis(ethylacetoacetate); di-isopropoxytitanium bis(ethylacetoacetate); and tetraalkyl titanates, such as tetra-n-butyl titanate and tetraisopropyl titanate. In one embodiment, the condensation catalyst (d) is diisopropyl diacetylacetonato titanium.

[0199] The crosslinking agent (e) of the present invention may be any crosslinking agent commonly used in elastomeric coatings, such as, by way of non-limiting example, alkoxysilanes, preferably polyalkoxysilanes.

[0200] In one embodiment, the optional cross-linking agent (e) has the general formula (VIII):

[0201] (R A ) x” R B y” Si(VIII)

[0202] Where R A and R B independently selected from monovalent C1-C 60 Hydrocarbon radicals, such as methyl, ethyl, propyl, isopropyl, butyl, tert-butyl, sec-butyl, etc., or alkoxy groups having 1-60 carbon atoms, and wherein x" is 2-4 and y" is 0-2, provided that x"+y"=4.

[0203] The optional crosslinking agent (e) may be selected from alkoxysilanes, epoxysilanes, mercaptosilanes, acrylate silanes, methacryloxysilanes, vinyl silanes, isocyanatosilanes, and combinations thereof.

[0204] An example of a polyalkoxysilane crosslinking agent (e) is methyltrimethoxysilane.

[0205] In one embodiment, component (a) is present in the elastomeric coating composition in an amount of about 5 wt % to about 95 wt %, preferably about 10 wt % to about 50 wt %, and more preferably about 15 wt % to about 40 wt %, based on the total weight of the elastomeric coating composition.

[0206] In one embodiment, in the elastomeric coating composition, component (b) is present in an amount of about 0.01 wt % to about 15 wt %, preferably about 0.05 wt % to about 10 wt %, and more preferably about 0.1 wt % to 7 wt %, and component (c) is present in an amount of about 2 wt % to about 20 wt %, preferably about 3 wt % to about 10 wt %, and more preferably 5 wt % to about 15 wt %, based on the added weight (total weight) of components (b) and (c).

[0207] In another non-limiting embodiment, the weight ratio of components (b) and (c) may range from about 1:300 to about 1:250, preferably about 1:200 to about 1:80, and even more preferably about 1:30 to about 1:20.

[0208] In one embodiment, component (d) is present in the elastomeric coating composition in an amount of about 0.01 wt % to about 5 wt %, preferably about 0.1 wt % to about 2.5 wt %, and even more preferably 0.5 wt % to about 2 wt %, based on the total weight of the elastomeric coating composition.

[0209] In one embodiment, optional component (e), if present, is present in the elastomeric coating composition in an amount of about 0.01 wt % to about 20 wt %, preferably about 0.5 wt % to about 15 wt %, and even more preferably about 1 wt % to about 10 wt %, based on the total weight of the elastomeric coating composition.

[0210] The elastomeric coating compositions of the present invention have demonstrated surprising and unexpected synergistic effects in stain resistance by using a combination of polyether silanes and fillers in the coating composition without adversely affecting other properties of the silicone coating.

[0211] More specifically, the elastomeric coating composition of the present invention has exhibited a synergistic effect of an enhanced level of anti-fouling properties of the elastomeric coating composition when both the surface wetting agent (b) and the filler (c) are used in the elastomeric coating composition, which enhanced anti-fouling properties are greater than the sum of the total increase in anti-fouling properties that occurs when only the surface wetting agent (b) or only the filler (c) is used together with the other components (a), (d) and optionally (e) of the elastomeric coating composition, i.e., the combination of (b) and (c) in the composition produces a level of anti-fouling properties that is greater than the sum of only (b) used alone and only (c) used alone.

[0212] The elastomeric coating composition of the present invention may also include additional additives such as solvents, adhesion promoters, pigments, anti-sagging agents, flame retardants, biocides, and the like.

[0213] In another embodiment, the adhesion promoter is an isocyanatosilane, for example an isocyanatosilane having the general formula (VI):

[0214]

[0215] Where R 37 is a divalent alkylene group having 1 to 10 carbon atoms, preferably 1 to 3 carbon atoms, R 38 is a monovalent hydrocarbon residue having 1 to 10 carbon atoms, preferably 1 to 3 carbon atoms, each Y is independently a member selected from a halogen atom, an alkoxy group having 1 to 10 carbon atoms, preferably 1 to 3 carbon atoms, an acryloxy group having 1 to 10 carbon atoms, preferably 1 to 3 carbon atoms, and v is a number of 1 to 3. In one embodiment, v is 3 and Y is an alkoxy group, preferably a methoxy group or an ethoxy group. In one embodiment, R 37 It is a divalent propyl group.

[0216] Some non-limiting examples of such isocyanatosilanes include, but are not limited to, α-isocyanatomethyltrimethoxysilane, β-isocyanatoethyltrimethoxysilane, -isocyanatopropyltrimethoxysilane, α-isocyanatomethyltriethoxysilane, β-isocyanatoethyltriethoxysilane, tris[3-(trimethoxysilyl)propyl]isocyanurate, and μ-isocyanatopropyltriethoxysilane, and combinations thereof.

[0217] A non-limiting example of such an isocyanatosilane is 3-isocyanatopropyltrimethoxysilane.

[0218] In one embodiment, non-limiting examples of adhesion promoters include, but are not limited to, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, n-ethyl-γaminoisobutyltrimethoxysilane, bis-[γ-(trimethoxysilyl)propyl]amine, bis-[γ-(triethoxysilyl)propyl]amine, 1,3,5-tris(trimethoxysilylpropyl)isocyanurate, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, aminopropyltrimethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, trisamino-functional trimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldiethoxysilane, methacryloxypropyltrimethoxysilane, methylaminopropyltrimethoxysilane. , γ-glycidyloxypropylethyldimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxyethyltrimethoxysilane, β-(3,4-epoxycyclohexyl)propyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, isocyanatopropyltriethoxysilane, isocyanatopropylmethyldimethoxysilane, β-cyanoethyltrimethoxysilane, γ-acryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, 4-amino-3,3-dimethylbutyltrimethoxysilane, n-ethyl-3-trimethoxysilyl-2-methylpropylamine, tris[3-(trimethoxysilyl)propyl]isocyanurate, and mixtures thereof.

[0219] The elastomeric coating composition of the present invention may include 0.5-40 weight percent of pigment, based on the total weight of the elastomeric coating composition. Pigments suitable for use in elastomeric coating compositions are generally known in the art and may include those described in The Kirk-Othmer Encyclopedia of Chemical Technology, Volume 17, John Wiley & Sons, Pages 1049-1069, (1996), ISBN 0-471-52686-X (which is incorporated herein by reference in its entirety). Inorganic or organic color pigments may be used, but inorganic pigments may be preferred because of their relatively low cost, better opacifying ability, and their exterior durability compared to organic pigments. White, black, and other colored pigments, such as titanium dioxide, may be used. Extender pigments, such as calcium carbonate, talc, clay, and silica, are also suitable.

[0220] The composition of the present invention can be used in various forms: as a liquid solution, a dispersion of a solid in a liquid, a dispersion of a liquid in a liquid, as an emulsion, a solid mixture or a solid solution, alone or in combination.

[0221] The elastomeric coating composition herein may be prepared by mixing the various components together. Preferably, the elastomeric coating composition is prepared by premixing component (a) and any resin and / or carrier, followed by addition of the other components.

[0222] Typically, for the purpose of emulsification, compatibilization of components, leveling, flow and reduction of surface defects, the coating formulation will require a wetting agent or surfactant. Although such components are not necessary, such additional optional additives can provide improvements in the cured or dried film, such as improved wear resistance, anti-blocking, hydrophilicity and hydrophobicity. The coating formulation of the present invention can exist as a solvent-based coating, a water-based (waterborne) coating and / or a powder coating.

[0223] The coatings of the present invention are suitable for use as architectural coatings, OEM product coatings (such as automotive coatings and coil coatings), and specialty coatings (such as industrial maintenance coatings and marine antifouling coatings).

[0224] In one aspect, the present invention may be directed to an architectural coating comprising the elastomeric coating composition described herein. In another aspect, the present invention may be directed to a single coat stain and / or antifouling and / or antifouling coating comprising the elastomeric coating composition described herein.

[0225] In one embodiment, the elastomeric coating composition may be used as a coating in addition to a sealant or adhesive for treating voids, cracks, seams or other abscesses in the architectural and / or engineering fields. Thus, the present invention may relate to the coating of a small portion (i.e. less than 50%) of a substrate surface or a large portion (i.e. more than 50%) of a substrate surface, such as an architectural element or a building facade, to provide a paint-like coating of said substrate, and does not relate to sealants used in filling or bonding the above-mentioned abscesses or similar ones known to those skilled in the art.

[0226] As used herein, the term "building element" refers to a prefabricated or manufactured unit used in a building construction, such as a window, particularly an insulating glass unit ("IGU"), a glass-paneled door, a door containing one or more windows, a prefabricated window, a sliding door having one or more windows, a folding door having one or more windows, a curtainwall, a shop glazing, a structural glazing, a skylight, a light fixture, etc., wherein the glazing is bonded to a structural element comprising the "building element" using an adhesive, a bedding glaze, a sealant, a caulking material or an adhesive composition.

[0227] In one embodiment, the substrate may include any material for which waterproofing and / or weathering protection may be sought on the face of a building or structure, such as concrete, brick, wood, metal, glass, plastic, stone, stucco, painted substrates, and the like.

[0228] In another embodiment, the amount of elastomeric coating applied to the substrate may depend on several factors, such as substrate type, temperature, humidity, desired degree of water resistance, and the specific components of the elastomeric coating composition. In one embodiment, the amount of coating is from about 10 to about 0.1 mm, preferably from about 5 to about 0.5 mm, and even more preferably from about 2 to about 0.2 mm.

[0229] The elastomeric coating composition may be applied by any means known and used by those skilled in the art such as by brushing, rolling or spraying.

[0230] The process of curing a surface (e.g., a substrate) coated with the elastomeric coating composition may include exposing the elastomeric coating composition to sufficient moisture to provide a cured coating on the substrate that cures the elastomeric coating composition. Such moisture may be applied by methods known to those skilled in the art or may simply include exposing the elastomeric coated surface to atmospheric moisture.

[0231] In an additional embodiment, the elastomeric coating on the substrate may have a Shore A hardness value of about 10 to about 60 according to ASTM C-661.

[0232] In one embodiment, the elastomeric coating on the substrate may have a tensile strength (measured as described herein) of about 1.0 to about 2.0, preferably about 1.10 to about 1.60, more preferably about 1.12 to about 1.45.

[0233] In another embodiment, the elastomeric coating on the substrate has an elongation (measured as described herein) of about 100% to about 400%, preferably about 140% to about 360%, and more preferably about 150% to about 350%.

[0234] In yet another embodiment, the elastomeric coating on the substrate may have a contact angle of about 70° to about 105°, and preferably about 75° to about 103°.

[0235] In yet another embodiment, the elastomeric coating on the substrate may have one or more of greater durability or UV resistance than a coating on the same substrate applied by the same coating composition except that only one of the surface wetting agent (b) or filler (c) but not both is present in the coating composition. In one embodiment, the coating on the substrate has a UV resistance of at least about 6 months, preferably at least about 9 months, more preferably at least about one year, and even more preferably at least about 5 years. UV resistance means that the coated substrate does not suffer from visible cracking, pitting, or peeling of the applied coating.

[0236] In yet another embodiment, the elastomeric coating on the substrate may provide a longer term (period) of water resistance protection than a coating of the same substrate applied by the same coating composition in which only one of the surface wetting agent (b) or filler (c) but not both is present in the coating composition. The water resistance protection may include water impermeability. In one embodiment, the term may be, for example, the term described for UV resistance.

[0237] In yet another embodiment, the elastomeric coating on the substrate can maintain the original appearance of the substrate for a longer period of time than the original appearance of the same substrate coated with the same coating composition wherein only one of the surface wetting agent (b) or filler (c) but not both is present in the coating composition.

[0238] In one embodiment, the elastomeric coating composition of the present invention can provide a substrate with protection against extreme temperatures. The extreme temperatures described herein can be below 40 degrees Fahrenheit, and more particularly below 20 degrees Fahrenheit. In another embodiment herein, the extreme temperatures described herein can be above 80 degrees Fahrenheit, particularly above 90 degrees Fahrenheit. The elastomeric coating composition herein can provide such extreme temperature protection, for example, for the duration described herein for UV resistance.

[0239] In one embodiment, the elastomeric coating on the substrate may have a dirt pick-up resistance (DPUR) as measured by the carbon slurry method described herein of about 30% to about 95% recovery, preferably about 33% to about 93% recovery, and even more preferably about 85% to about 93% recovery.

[0240] In another embodiment, the elastomeric coating on the substrate may have a DPUR as measured by the carbon slurry method described herein of about 40% to about 95% recovery, preferably about 45% to about 93% recovery, more preferably about 80% to about 93% recovery, and even more preferably about 85% to about 93% recovery.

[0241] The elastomeric coating composition of the present invention can be used as a coating material for buildings, such as building facades, wherein the waterproofing and / or weathering protection of the coated material can be used to protect and maintain the original appearance of the building facade.

[0242] In another embodiment, an emulsion comprising the elastomeric coating composition is provided. In another embodiment, the emulsion is a non-aqueous silicone emulsion.

[0243] In another aspect, the present invention is directed to a method of treating a building facade comprising applying the elastomeric coating composition to the exterior of the building facade, and curing the coating composition to provide a cured coating on the building facade.

[0244] A building facade including the cured coating is also provided.

[0245] The following non-limiting examples further describe and disclose the present invention.

[0246] Example

[0247] Example 1 :

[0248] 15.44 parts by weight of a hydroxyl terminated polydimethylsiloxane polymer having a viscosity of 3,000 centipoise (cps) at 25°C, 16.87 parts by weight of a hydroxyl terminated polydimethylsiloxane polymer having a viscosity of 30,000 centipoise (cps) at 25°C, 2.18 parts by weight of methyltrimethoxysilane were blended in a planetary mixer at 75°C under anhydrous conditions for 1 hour. 38.06 parts by weight of treated ground calcium carbonate, 2.02 parts by weight of titanium dioxide, 3.68 parts by weight of fumed silica treated with hexamethyldisilazane were added to the above mixture until a good dispersion was obtained. A degassing vacuum was applied for 15 minutes. 20.17 parts by weight of CONOSOL C-200 (aliphatic hydrocarbon solvent available at Calumet Penreco LLC.), 1.15 parts by weight of titanium ethylacetoacetate, 0.43 parts by weight of 1,3,5-tris(3-methoxysilylpropyl)isocyanurate were added to the above dispersion and mixed under nitrogen.

[0249] To evaluate mechanical properties, the mixture was wet drawn on a Teflon-coated glass plate at a thickness of 600 microns and dried for 7 days. The film was peeled off and cut in length into rectangular strips of 10 mm wide and 50 mm long. The mechanical properties were measured using an Instron 3365, a mechanical testing machine (which can Mechanical properties were tested by tensile tester. For hardness measurement, 10 mm thick films were prepared.

[0250] Tensile strength: 1.14Mpa

[0251] Elongation: 340%

[0252] Hardness (Shore A): 27

[0253] Contact angle: 98.5

[0254] To evaluate the DPUR properties, the mixture was wet stretched on glass in a 300 μm thick film and stored at 23° C., 50% relative humidity for 7 days, and then tested according to the test method described below.

[0255] DPUR test method : A film having a desired thickness was stretched on a glass plate and dried at room temperature for 7 days. Gretag Macbeth Color Eye 7000A (which can be found in Inc.) to measure the L b Value. Dry carbon black powder and a slurry of carbon black in water (15% wt / wt) were used as the dirt media and were applied to the membrane using a brush, respectively. The membrane was dried at 50°C for 1 h using a hot air oven and then washed with tap water and cheese cloth for 3 minutes. The final L of the exposed membrane was measured. a Value. Use the formula [100-((L b -L a )*100 / L b )] Calculate the percentage recovery rate (DPUR) of the whiteness (L) of the coating.

[0256] Example 2 :

[0257] 81.81 parts by weight of the material from Example-1 was taken in a mixing container, 9.09 parts by weight of mica (wet processed) and 9.09 parts by weight of MPRL D60 (aliphatic hydrocarbon solvent available from Metha Petro Refinary Ltd) were added and mixed in nitrogen atmosphere for 10 minutes using a high speed planetary mixer.

[0258] To evaluate mechanical properties, the mixture was wet stretched on a Teflon-coated glass plate at a thickness of 600 microns and allowed to dry for 7 days. The film was peeled off and cut in length into rectangular strips 10 mm wide and 50 mm long. The results were obtained using an Instron 3360 (which can Mechanical properties were tested using a mechanical testing machine. For hardness measurement, 10 mm thick films were prepared.

[0259] Tensile strength: 1.40Mpa

[0260] Elongation: 154%

[0261] Hardness (Shore A): 55

[0262] Contact angle: 101.5

[0263] To evaluate the DPUR properties, the mixture was wet stretched on a glass panel at a thickness of 300 micrometers and stored at 23°C, 50% relative humidity for 7 days, and then tested according to the above test method.

[0264] Example 3 :

[0265] 80.57 parts by weight of the material from Example-1 was taken in a mixing container, 8.95 parts by weight of mica (wet processed), 1.52 parts by weight of SILQUEST A-1230 silane (available from Momentive Performance Materials Inc.) and 8.95 parts by weight of MPRL D60 were added and mixed in a nitrogen atmosphere for 10 minutes using a high speed planetary mixer.

[0266] To evaluate mechanical properties, the mixture was wet stretched at 600 micron thickness on a Teflon coated glass plate and dried for 7 days. The film was peeled off and cut into rectangular strips 10 mm wide and 50 mm long in length. Mechanical properties were tested using an Instron 3365. For hardness measurements, 10 mm thick films were prepared.

[0267] Tensile strength: 1.41Mpa

[0268] Elongation: 160%

[0269] Hardness (Shore A): 54

[0270] Contact angle: 79.3

[0271] To evaluate the DPUR properties, the mixture was wet stretched at a thickness of 300 micrometers on a glass panel and stored at 23°C, 50% relative humidity for 7 days, and then tested according to the above test method.

[0272] Example 4 :

[0273] 98.48 parts by weight of the material from Example-1 was taken in a mixing container and 1.52 parts by weight of SILQUEST A-1230 silane was added and mixed using a high speed planetary mixer in a nitrogen atmosphere for 10 minutes.

[0274] To evaluate mechanical properties, the mixture was wet stretched at 600 micron thickness on a Teflon coated glass plate and dried for 7 days. The film was peeled off and cut into rectangular strips of 10 mm wide and 50 mm long in length. Mechanical properties were tested using an Instron 3365 tensile tester. For hardness measurements, a 10 mm thick film was prepared.

[0275] Tensile strength: 1.14Mpa

[0276] Elongation: 350%

[0277] Hardness (Shore A): 27

[0278] Contact angle: 85.5

[0279] To evaluate the DPUR properties, the mixture was wet stretched as a 300 μm thick film on glass and stored at 23° C., 50% relative humidity for 7 days and then tested according to the above test method.

[0280] Example 5 :

[0281] 80.57 parts by weight of the material from Example-1 was placed in a mixing container, 8.95 parts by weight of mica (wet treated), 0.626 parts by weight of SILQUEST A-1230 silane, 0.895 parts by weight of SILQUEST A-LINK35 silane (available from Momentive Performance Materials Inc.) and 8.95 parts by weight of MPRL D60 were added and mixed in a nitrogen atmosphere for 10 minutes using a high-speed planetary mixer.

[0282] To evaluate mechanical properties, the mixture was wet stretched at 600 micron thickness on a Teflon coated glass plate and dried for 7 days. The film was peeled off and cut into rectangular strips 10 mm wide and 50 mm long in length. Mechanical properties were tested using an Instron 3365. For hardness measurements, 10 mm thick films were prepared.

[0283] To evaluate the DPUR properties, the mixture was wet stretched as a 300 μm thick film on glass and stored at 23° C., 50% relative humidity for 7 days and then tested according to the above test method.

[0284] Tensile strength: 1.44Mpa

[0285] Elongation: 156%

[0286] Hardness (Shore A): 57

[0287] Contact angle: 82

[0288] Example 6 :

[0289] 80.57 parts by weight of the material from Example-1 was taken in a mixing container, 8.95 parts by weight of mica (wet processed), 1.52 parts by weight of dihydroxy terminated ethylene oxide polymer (molecular weight 400 Dalton) and 8.95 parts by weight of MPRL D60 were added and mixed in a nitrogen atmosphere for 10 minutes using a high speed planetary mixer.

[0290] To evaluate the DPUR properties, the mixture was wet stretched as a 300 μm thick film on glass and stored at 23° C., 50% relative humidity for 7 days and then tested according to the above test method.

[0291] Tensile strength: NM

[0292] Elongation: NM

[0293] Hardness (Shore A): 52

[0294] Contact angle: about 78-85

[0295] NM = Not Measured

[0296] Example 7 :

[0297] 80.57 parts by weight of the material from Example-1 were taken in a mixing container, 8.95 parts by weight of mica (wet processed), 0.626 parts by weight of dihydroxy terminated ethylene oxide polymer (molecular weight 400 Dalton), 0.895 parts by weight of SILQUEST A-LINK 35 silane and 8.95 parts by weight of MPRL D60 were added and mixed in a nitrogen atmosphere for 10 minutes using a high speed planetary mixer.

[0298] To evaluate the DPUR properties, the mixture was wet stretched as a 300 μm thick film on glass and stored at 23° C., 50% relative humidity for 7 days and then tested according to the above test method.

[0299] Tensile strength: NM

[0300] Elongation: NM

[0301] Hardness (Shore A): 55

[0302] Contact angle: about 79-85

[0303] Example 8 :

[0304] 81.88 parts by weight of the material from Example 1 was placed in a mixing container, and 9.09 parts by weight of 3M TM Ceramic microspheres W-210 (solid, white, fine spherical particles with a typical whiteness (L value) of 95 or more and a particle size of 3 microns, used in architectural paints from 3M India Limited) and 9.09 parts by weight of MPRL D60 were mixed in a nitrogen atmosphere for 10 minutes using a high-speed planetary mixer.

[0305] To evaluate the DPUR properties, the mixture was wet stretched as a 300 μm thick film on glass and stored at 23° C., 50% relative humidity for 7 days and then tested according to the above test method.

[0306] Tensile strength: NM

[0307] Elongation: NM

[0308] Hardness (Shore A): 55

[0309] Contact angle: about 98-102

[0310] Example 9 :

[0311] 80.57 parts by weight of the material from Example 1 was placed in a mixing container, and 8.95 parts by weight of 3M TM Ceramic microspheres W-210 (solid, white, fine spherical particles with a typical whiteness (L value) of 95 or more and a particle size of 3 microns, used in architectural paints), 1.52 parts by weight of a nonionic polymer fluorochemical surfactant FC 4430 from 3M Company, and 8.95 parts by weight of MPRL D60 were mixed and mixed in a nitrogen atmosphere for 10 minutes using a high-speed planetary mixer.

[0312] To evaluate the DPUR properties, the mixture was wet stretched as a 300 μm thick film on glass and stored at 23° C., 50% relative humidity for 7 days and then tested according to the above test method.

[0313] Tensile strength: NM

[0314] Elongation: NM

[0315] Hardness (Shore A): 55

[0316] Contact angle: about 98-102

[0317] Example 10 :

[0318] 80.57 parts by weight of the material from Example 1 was placed in a mixing container, and 8.95 parts by weight of 3M TM Ceramic microspheres W-210 (solid, white, fine spherical particles with a typical whiteness (L value) of 95 or more and a particle size of 3 microns, used in architectural paints), 1.52 parts by weight of a nonionic polymer fluorochemical surfactant FC 4434 from 3M Company, and 8.95 parts by weight of MPRL D60 were mixed and mixed in a nitrogen atmosphere for 10 minutes using a high-speed planetary mixer.

[0319] To evaluate the DPUR properties, the mixture was wet stretched as a 300 μm thick film on glass and stored at 23° C., 50% relative humidity for 7 days and then tested according to the above test method.

[0320] Tensile strength: NM

[0321] Elongation: NM

[0322] Hardness (Shore A): 55

[0323] Contact angle: about 98-102

[0324] Embodiment 11 :

[0325] 80.57 parts by weight of the material from Example-1 was taken in a mixing container, 8.95 parts by weight of mica (wet treated), 1.52 parts by weight of SILQUEST A-LINK 35 silane and 8.95 parts by weight of MPRL D60 were added and mixed in a nitrogen atmosphere for 10 minutes using a high speed planetary mixer.

[0326] To evaluate the DPUR properties, the mixture was wet stretched as a 300 μm thick film on glass and stored at 23° C., 50% relative humidity for 7 days and then tested according to the above test method.

[0327] Tensile strength: NM

[0328] Elongation: NM

[0329] Hardness (Shore A): 57

[0330] Contact angle: about 95-101

[0331] Example 12 :

[0332] 80.57 parts by weight of the material from Example-1 was taken in a mixing container, 8.95 parts by weight of mica (dry processed), 1.52 parts by weight of SILQUEST A-1230 silane and 8.95 parts by weight of MPRL D60 were added and mixed in a nitrogen atmosphere for 10 minutes using a high speed planetary mixer.

[0333] To evaluate the DPUR properties, the mixture was wet stretched as a 300 μm thick film on glass and stored at 23° C., 50% relative humidity for 7 days and then tested according to the above test method.

[0334] Tensile strength: NM

[0335] Elongation: NM

[0336] Hardness (Shore A): 52

[0337] Contact angle: about 80-90

[0338] Example 13 :

[0339] A mixture of 8.8 parts by weight of mica (wet processed) and 0.8 parts by weight of polyether functionalized PDMS was mixed in a speed mixer at 2350 RPM for 10 minutes and the mixture was mixed with 90.4 parts by weight of the material from Example-1 in a nitrogen atmosphere using a high speed planetary mixer for 10 minutes.

[0340] To evaluate the DPUR properties, the mixture was wet stretched as a 300 μm thick film on glass and stored at 23° C., 50% relative humidity for 7 days and then tested according to the above test method.

[0341] Embodiment 14 :

[0342] A mixture of 8.8 parts by weight of mica (wet processed) and 1.2 parts by weight of polyether functionalized PDMS was mixed in a mixer at 2350 RPM for 10 minutes and mixed with 90 parts by weight of the material from Example-1 in a nitrogen atmosphere for 10 minutes using a high speed planetary mixer.

[0343] To evaluate the DPUR properties, the mixture was wet stretched as a 300 μm thick film on glass and stored at 23° C., 50% relative humidity for 7 days and then tested according to the above test method.

[0344] Embodiment 15 :

[0345] A mixture of 8.8 parts by weight of mica (wet processed) and 1.2 parts by weight of polyether functionalized trisiloxane was mixed in a mixer at 2350 RPM for 10 minutes and the mixture was mixed with 90 parts by weight of material from Example-1 in a nitrogen atmosphere using a high speed planetary mixer for 10 minutes.

[0346] To evaluate the DPUR properties, the mixture was wet stretched as a 300 μm thick film on glass and stored at 23° C., 50% relative humidity for 7 days and then tested according to the above test method.

[0347] Example 16 :

[0348] A mixture of 8 parts by weight of mica (wet processed) and 4 parts by weight of low molecular weight hydroxyl terminated PDMS was mixed in a mixer at 2350 RPM for 10 minutes, and the mixture was mixed with 88 parts by weight of the material from Example-1 in a nitrogen atmosphere for 10 minutes using a high speed planetary mixer.

[0349] To evaluate the DPUR properties, the mixture was wet stretched as a 300 μm thick film on glass and stored at 23° C., 50% relative humidity for 7 days and then tested according to the above test method.

[0350] Embodiment 17 :

[0351] A mixture of 8 parts by weight of mica (wet processed) and 8 parts by weight of low molecular weight hydroxyl terminated PDMS was mixed in a mixer at 2350 RPM for 10 minutes and the mixture was mixed with 84 parts by weight of the material from Example-1 in a nitrogen atmosphere using a high speed planetary mixer for 10 minutes.

[0352] To evaluate the DPUR properties, the mixture was wet stretched as a 300 μm thick film on glass and stored at 23° C., 50% relative humidity for 7 days and then tested according to the above test method.

[0353] Embodiment 18 :

[0354] A mixture of 8 parts by weight of mica (wet processed) and 10 parts by weight of high molecular weight hydroxy-terminated PDMS (viscosity of 30,000 cps) was mixed in a mixer at 2350 RPM for 10 minutes, and the mixture was mixed with 82 parts by weight of the material from Example-1 in a nitrogen atmosphere for 10 minutes using a high-speed planetary mixer.

[0355] To evaluate the DPUR properties, the mixture was wet stretched as a 300 μm thick film on glass and stored at 23° C., 50% relative humidity for 7 days and then tested according to the above test method.

[0356] Embodiment 19 :

[0357] A mixture of 8 parts by weight of mica (wet processed) and 8 parts by weight of eugenol terminated PDMS was mixed in a mixer at 2350 RPM for 10 minutes and the mixture was mixed with 84 parts by weight of the material from Example-1 in a nitrogen atmosphere for 10 minutes using a high speed planetary mixer.

[0358] To evaluate the DPUR properties, the mixture was wet stretched as a 300 μm thick film on glass and stored at 23° C., 50% relative humidity for 7 days and then tested according to the above test method.

[0359] Examples 20-24 :

[0360] A mixture of 8 parts by weight of mica (wet treated) and 2 / 4 / 8 / 10 parts by weight of dimethoxy-methyl terminated PDMS for Examples 21-25, respectively, was mixed in a mixer at 2350 RPM for 10 minutes, and the mixture was mixed with 90 / 88 / 84 / 82 parts by weight of the material from Example-1 for Examples 20-24, respectively, in a nitrogen atmosphere using a high-speed planetary mixer for 10 minutes.

[0361] To evaluate DPUR properties, the mixture was wet stretched as a 300 micron thick film on glass and stored at 23°C, 50% relative humidity for 7 days and then tested according to the above test method except that the cheesecloth wipe was not performed in the slurry method.

[0362] DPUR Results:

[0363] Table 1

[0364]

[0365] DPUR test by UV exposure:

[0366] As described in Example 1, the films for DPUR testing were prepared and after curing for 7 days, they were exposed to a UV environment for 4 hours using a UVA lamp with an irradiance of 0.89 W / (m2-nm) by a UV Test Fluorescent / UV instrument from Atlas, and the whiteness recovery is shown in the following table:

[0367] Table 2

[0368]

[0369] Stain resistance results :

[0370] The mixture was wet stretched as a 300 micron thick film on Leneta paper (available from Leneta Company Inc.) and dried at 23°C for 7 days. Different colorings were applied on the substrate and dried at 25°C for 24 hours. The coloring was washed with tap water using a soft scrubbing pad. A rating was provided based on the surface cleanliness with respect to the coloring.

[0371] Table 3

[0372]

[0373] Acid / Alkali Resistance Results :

[0374] Acid / base water and paste were applied to the substrate and dried at room temperature for 24 h. The coloring was washed with water by gently wiping. The results are recorded below:

[0375] Table 4

[0376]

[0377] Viscosity and spreading rate:

[0378] For the formulations of the invention, better spreading was observed

[0379] Table 5

[0380] Example Viscosity (Pas) Spreading rate (sqf / kg) Example-1 5.76 47.602 Example-2 5.85 52.743 Example-3 5.80 55.643 Example-5 5.85 55.534 Commercially available elastomeric coatings 4.50 63.802

[0381] Fatigue test results of elastomeric coatings:

[0382] During the time-dependent temperature changes, cracks appear in concrete structures due to expansion and contraction. This test is performed to understand the resilience of elastomeric coatings during repeated compression (stress) and relaxation cycles. This test reflects the durability of the coating during expansion and contraction of the concrete substrate. The test is performed using an Instron 3365 with repeated elongation and relaxation cycles of 50% of its original length. More cycles reflect better coating performance.

[0383] The formulation of Example 3 and the industrial elastomeric paint were wet stretched at a thickness of 600 microns on a Teflon-coated glass plate and dried for 7 days. The film was peeled off and cut in length into rectangular strips 10 mm wide and 20 mm long. The test was stopped after 20 cycles.

[0384] Table 6

[0385]

[0386] Although the present invention has been described with reference to certain embodiments, it will be appreciated by those skilled in the art that various changes may be made and that equivalents may be substituted for its elements without departing from the scope of the present invention. In addition, many changes may be made to adapt a particular scenario or material to the teachings of the present invention without departing from its essential scope. Therefore, it is contemplated that the present invention is not limited to the specific embodiments disclosed as the best mode contemplated for carrying out the present invention, but that the present invention will include all embodiments falling within the scope of the appended claims.

Claims

1. An elastomeric coating composition comprising: a) at least one condensation-polymerizable polymer of formula (I) having two or more silicon atoms; M 1 a M 2 b M 3 c M 4 d D 1 e D 2 f D 3 g D 4 h (I) in: M 1 =R 1 R 2 R 3 SiO 1 / 2 M 2 =R 4 R 5 R 6 SiO 1 / 2 M 3 =R 7 R 8 R 9 SiO 1 / 2 M 4 =R 10 R 11 R 12 SiO 1 / 2 D 1 =R 13 R 14 SiO 2 / 2 D 2 =R 15 R 16 SiO 2 / 2 D 3 =R 17 R 18 SiO 2 / 2 D 4 =R 19 R 20 SiO 2 / 2 Among them, R 1 and R 13 Each is independently an aliphatic group or an aromatic group having 1 to 60 carbon atoms, OH or -H or OR 25 , where R 25 is an aliphatic or aromatic group having 1 to 60 carbon atoms; R 2 , R 3 , R 5 , R 6 , R 8 , R 9 , R 10 , R 11 , R 12 , R 14 , R 16 , R 18 , R 19 and R 20 Each independently is an aliphatic or aromatic group having 1 to 60 carbon atoms; R 4 and R 15 Each independently is as follows: -(C n H 2n )-O-(C2H4O) o -(C3H6O) p -(C4H8O) q -R 26 , where R 26 is hydrogen or an aliphatic or aromatic group having 1-60 carbon atoms, n is 0-6, o is 0-100, p is 0-100, and q is 0-50, provided that o+p+q≥0; R 7 and R 17 are each independently a branched, linear or cyclic saturated or unsaturated alkyl group having 4 to 36 carbon atoms, and The subscripts a, b, c, d, e, f, g, h are each independently zero or a positive integer, and the prerequisite is that a+b+c+d+e+f+g+h≥2, and a+b+c+d=2, and a+e≥2, and Provided that the polymer of formula (I) comprises a group consisting of -OH, -OR 25 and combinations thereof of at least two groups; b) a surface wetting agent comprising a polyoxyalkylene-containing silane comprising an aliphatic hydrocarbon moiety between the silicon atom and the polyoxyalkylene moiety of the polyoxyalkylene-containing silane; c) at least one filler comprising mica; and, d) a condensation catalyst, wherein the surface wetting agent (b) further comprises a functional siloxane selected from the group consisting of polyether functionalized polydimethylsiloxane, polyether functionalized trisiloxane, low molecular weight end-blocked polydimethylsiloxane having a viscosity of 2,000-10,000 cps, high molecular weight end-blocked polydimethylsiloxane having a viscosity of 30,000-40,000 cps, eugenol end-blocked polydimethylsiloxane, dimethoxy-methyl end-blocked polydimethylsiloxane, methyl end-blocked polydimethylsiloxane, and combinations thereof, The polyether functionalized trisiloxane is represented by the following formula: wherein Me means methyl; Z is an alkyl group containing 1 to 4 carbon atoms and m* and n* are each 0 to 10; The polyether functionalized polydimethylsiloxane is represented by the formula: wherein Z is an alkyl group having 1 to 4 carbon atoms, m* and n* are each 0 to 10, and x'+y' is 1 to 20; Eugenol-terminated polydimethylsiloxane is represented by the following formula: Where y* is 1-60; The low molecular weight blocked polydimethylsiloxane having a viscosity of 2,000-10,000 cps and the high molecular weight blocked polydimethylsiloxane having a viscosity of 30,000-40,000 cps are represented by the following formula: Where y# is 10-1,000; Dimethoxy-methyl terminated polydimethylsiloxane: Where n# is 1-20; Methyl terminated polydimethylsiloxane is represented by the following formula: Where n' is 10-300.

2. The elastomeric coating composition of claim 1, wherein the at least one condensation-polymerizable polymer having two or more silicon atoms (a) is selected from the group consisting of hydroxyl-terminated polydimethylsiloxanes, alkoxy-terminated polydimethylsiloxanes, and combinations thereof.

3. The elastomeric coating composition of claim 1, wherein the at least one condensation-polymerizable polymer (a) having two or more silicon atoms is a silanol-terminated polydiorganosiloxane wherein each organic moiety is independently an alkyl group of 1 to 6 carbon atoms.

4. The elastomeric coating composition of claim 1, wherein the polyoxyalkylene-containing silane is selected from the general formula (II) and / or (III), wherein formula (II) is: Where R 27 independently selected from alkyl groups having 1 to 12 carbon atoms; R 28 A portion selected from the following: in represents the bonds connecting the silicon atoms of the structure of formula (II); R 29 independently selected from hydrogen or an alkyl group having 1 to 4 carbon atoms, or -COR 33 ; R 33 independently selected from hydrogen or an alkyl group having 1 to 16 carbon atoms; R 30 independently selected from hydrogen or an alkyl group having 1 to 4 carbon atoms; R 31 independently selected from divalent alkylene groups having 1 to 4 carbon atoms; R 32 independently selected from divalent carbamate, acrylamide, amide or urea groups; and, r is 1-100 and x is zero or 1; Wherein formula (III): Where R 27 as previously defined; Z is independently selected from divalent carbamate, acrylamide, amide or urea groups; s and t are independently integers from 0 to 2; L is independently selected from divalent aliphatic linear hydrocarbon groups having 2 to 15 carbon atoms and optionally having oxygen or nitrogen atoms at one or two valence bonds; R 34 Defined by general formula (IV): Where R 35 independently selected from hydrogen or an alkyl group having 1 to 4 carbon atoms; x is as previously defined; and, u is an integer from 1 to 100.

5. The elastomeric coating composition of claim 1, wherein the surface wetting agent (b) further comprises one or more selected from the group consisting of: Functionalized organosiloxane of general formula (V): Where R 39 , R 42 , R 43 , R 44 , R 45 , R 46 , R 47 , R 49 and R 50 independently selected from hydrogen, an alkyl group containing 1 to 10 carbon atoms, or an alkoxy group containing 1 to 10 carbon atoms; R 40 Selected from hydrogen, alkyl groups containing 1 to 10 carbon atoms, alkoxy groups containing 1 to 10 carbon atoms, heteroatom-containing compounds containing 1 to 10 carbon atoms, wherein m, n and o are each independently an integer of 0 to 1000; and Compounds of formula (VII) R j 41 -ZR k 41 -Z-R1 41 (VII) Where R 41 independently selected from hydrogen or an alkyl group having 1 to 10 carbon atoms or a heteroatom-containing compound having 1 to 10 carbon atoms; Z is a heteroatom, and j, k and 1 are each independently an integer from 0 to 10, and R 48 and R 51 Independently selected from hydrogen, or hydroxy, or alkyl or alkoxy having 1 to 10 carbon atoms, or substituted or unsubstituted aromatic compounds containing 6 to 20 carbon atoms.

6. The elastomeric coating composition of claim 1, wherein the at least one filler (c) further comprises a layered structural filler selected from the group consisting of clay, ground calcium carbonate, precipitated calcium carbonate, colloidal calcium carbonate, calcium carbonate treated with a compound containing a stearate moiety or stearic acid, fumed silica, precipitated silica, crushed quartz, quartz powder, alumina, aluminum hydroxide, titanium hydroxide, kaolin, bentonite, montmorillonite, diatomaceous earth, iron oxide, carbon black and graphite, talc, pumice, wollastonite, ceramics, glass beads, PTFE, and combinations thereof.

7. The elastomeric coating composition of claim 1, wherein the mica is wet processed mica.

8. The elastomeric coating composition of claim 1, wherein the filler (c) is mica.

9. The elastomeric coating composition of claim 1, wherein the surface wetting agent (b) is an ethylene oxide and / or propylene oxide containing silane and the filler (c) is mica.

10. The elastomeric coating composition of claim 1, wherein the condensation catalyst (d) is a titanium catalyst.

11. The elastomeric coating composition of claim 1 wherein the condensation catalyst (d) is titanium diisopropyl diacetylacetonate.

12. The elastomeric coating composition of claim 1, further comprising a crosslinking agent (e).

13. The elastomeric coating composition of claim 12, wherein the crosslinking agent (e) is selected from the group consisting of alkoxysilanes, epoxysilanes, mercaptosilanes, acrylate silanes, methacryloxysilanes, vinyl silanes, isocyanatosilanes, and combinations thereof.

14. The elastomeric coating composition of claim 12, wherein the crosslinking agent (e) is methyltrimethoxysilane.

15. The elastomeric coating composition of claim 1 further comprising an adhesion promoter selected from the group consisting of tris[3-(trimethoxysilyl)propyl]isocyanurate, 3-isocyanatopropyltrimethoxysilane, α-isocyanatomethyltrimethoxysilane, β-isocyanatoethyltrimethoxysilane, γ-isocyanatopropyltrimethoxysilane, α-isocyanatomethyltriethoxysilane, β-isocyanatoethyltriethoxysilane, and μ-isocyanatopropyltrimethoxysilane. Isocyanatosilane of acylopropyltriethoxysilane, 1,3,5-tris(trimethoxysilylpropyl)isocyanurate, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-ethyl-γaminoisobutyltrimethoxysilane, bis-[γ-(trimethoxysilyl)propyl]amine, bis-[γ-(triethoxysilyl)propyl]amine, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, aminopropyltrimethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, triaminofunctional trimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldiethoxysilane, methacryloxypropyltrimethoxysilane, methylaminopropyltrimethoxysilane, γ-glycidoxypropylethyldimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxyethyltrimethoxysilane, β-(3,4-epoxycyclohexyl)propyltrimethoxysilane Oxysilane, β-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, isocyanatopropyltriethoxysilane, isocyanatopropylmethyldimethoxysilane, β-cyanoethyltrimethoxysilane, γ-acryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, 4-amino-3,3-dimethylbutyltrimethoxysilane, n-ethyl-3-trimethoxysilyl-2-methylpropylamine, or a combination thereof.

16. The elastomeric coating composition of claim 1, wherein the adhesion promoter is a heteroatom-containing silane having the general formula (VI): Where R 37 is a divalent alkylene group having 1 to 10 carbon atoms, R 38 is a monovalent hydrocarbon residue having 1-10 carbon atoms, each Y is independently selected from a halogen atom, an alkoxy group having 1-10 carbon atoms, and an acryloyloxy group having 1-10 carbon atoms, and v is 1-3.

17. The elastomeric coating composition of claim 6, wherein the clay is a nanoclay.

18. The elastomeric coating composition of claim 6, wherein the clay is an organoclay.

19. An architectural coating comprising the elastomeric coating composition of claim 1.

20. A one-time stain and / or antifouling and / or antifouling coating comprising the elastomeric coating composition of claim 1.

21. A method for preparing an elastomeric coating composition, comprising combining: a) at least one condensation-polymerizable polymer having two or more silicon atoms as defined in claim 1; b) a surface wetting agent comprising a polyoxyalkylene-containing silane comprising an aliphatic hydrocarbon moiety between the silicon atom and the polyoxyalkylene moiety in the polyoxyalkylene-containing silane; c) at least one filler comprising mica; and, d) Condensation catalyst.

22. The method of claim 21, wherein the mica is wet processed mica.

23. The method of claim 21, wherein the surface wetting agent is a silane containing ethylene oxide and / or propylene oxide.

24. An elastomeric coating composition consisting of: a) at least one condensation-polymerizable polymer of formula (I) having two or more silicon atoms; M 1 a M 2 b M 3 c M 4 d D 1 e D 2 f D 3 g D 4 h (I) in: M 1 =R 1 R 2 R 3 SiO 1 / 2 M 2 =R 4 R 5 R 6 SiO 1 / 2 M 3 =R 7 R 8 R 9 SiO 1 / 2 M 4 =R 10 R 11 R 12 SiO 1 / 2 D 1 =R 13 R 14 SiO 2 / 2 D 2 =R 15 R 16 SiO 2 / 2 D 3 =R 17 R 18 SiO 2 / 2 D 4 =R 19 R 20 SiO 2 / 2 Among them, R 1 and R 13 Each is independently an aliphatic group or an aromatic group having 1 to 60 carbon atoms, OH or -H or OR 25 , where R 25 is an aliphatic or aromatic group having 1 to 60 carbon atoms; R 2 , R 3 , R 5 , R 6 , R 8 , R 9 , R 10 , R 11 , R 12 , R 14 , R 16 , R 18 , R 19 and R 20 Each independently is an aliphatic or aromatic group having 1 to 60 carbon atoms; R 4 and R 15 Each independently is as follows: -(C n H 2n )-O-(C2H4O) o -(C3H6O) p -(C4H8O) q -R 26 , where R 26 is hydrogen or an aliphatic or aromatic group having 1-60 carbon atoms, n is 0-6, o is 0-100, p is 0-100, and q is 0-50, provided that o+p+q≥0; R 7 and R 17 are each independently a branched, linear or cyclic saturated or unsaturated alkyl group having 4 to 36 carbon atoms, and The subscripts a, b, c, d, e, f, g, h are each independently zero or a positive integer, and the prerequisite is that a+b+c+d+e+f+g+h≥2, and a+b+c+d=2, and a+e≥2, and Provided that the polymer of formula (I) comprises a group consisting of -OH, -OR 25 and combinations thereof of at least two groups; b) a surface wetting agent comprising a polyoxyalkylene-containing silane comprising an aliphatic hydrocarbon moiety between the silicon atom and the polyoxyalkylene moiety of the polyoxyalkylene-containing silane; c) at least one filler comprising mica; and, d) Condensation catalyst.

Citation Information

Patent Citations

  • Antifouling coating composition, antifouling coating film, antifouling substrate, and method for improving storage stability of antifouling coating composition

    CN104781356A